Basic and Higher Education Teachers´ Technological Enablement - Alberto Ramírez Martinell; Miguel Ángel Casillas Alvarado; Ingrid Rubí Aguirre (Universidad de Guadalajara, 2018)
In this article we present the revision of trends and general implications of Higher education and continuous education of educators in distance mode in México -in the first place- and in the State of Veracruz -in the second place-, Mexican State where distance education enhanced with digital mediation has been a clear option of student and educator´s formation with a considerable reach. Technology enablement of educators with digital means is every time more necessary and to be coherent with the signs of the times, it requires breaking the prevailing paradigm of what it is understood by computational competence. As a response to a change of an educator´s enablement structure, we built two virtual diplomats for in service educators that have, as a funding base, the theory of the Digital Knowledge Set. The courses that were designed in 2017 and 2018, are today offered by the National Association of Universities and Higher Education Institutions of Mexico and its National System of Distance Education; and besides resorting to the afore mentioned theory, the programs considered the level educators are working on and their disciplinary orientation as articulation axis of a relevant bildung.